(untitled) (Journal of Nepal Geological Society, 1999)
Clay mineral assemblages in the Ariyalur Group of sedimentary rocks were studied by X-ray diffraction analysis. The results of the study indicate that illite and smectite are the predominant clay minerals whereas kaolinite and chlorite occur in minor amounts. The Campanian-Lower Maastrichtian rocks (i.e., Sillakkudi and Kallankurichchi Formations) contain a large amount of illite. The study reveals that these sediments were derived from the continental erosion of pre-existing rocks that were subjected to low intensity chemical weathering associated with a temperate climate. A significant decrease in illite content is observed in the Ottakkovil Formation. It implies a climatic transition (from temperate to warm) during the Middle Maastrichtian time. On the other hand, a high content of pedogenic smectite in the Kallamedu Formation is indicative of warm climatic conditions with alternating dry and wet periods during the formation of this mineral.